SITIOS COSTARRICENSES DE NOTICIAS EN FACEBOOK: ¿QUÉ “LIKEAN”, COMENTAN Y COMPARTEN SUS USUARIOS? - Siles González, Ignacio (2018)
This paper discusses how users interact with news content published by Costa Rican online news sites on Facebook. Drawing on a mixed-method research design that combined social network analysis and content analysis, we examined the data published by six major Costa Rican news sites during four months of 2016. We identified a clear user preference for content about non-public affair issues, such as crimes, sports, and entertainment. In contrast, news about public affairs, such as politics, economy, and government, received relatively much less interaction. We also examined a structural difference in how users interacted with the content published by news sites. We conclude with a discussion of the analytical opportunities afforded by the circulation of news on Facebook.